From spikes to intercellular waves: Tuning intercellular calcium signaling dynamics modulates organ size control. - Soundarrajan, D.K.; Huizar, F.J.; Paravitorghabeh, R.; Robinett, T.; Zartman, J.J. (PLoS Computational Biology, 2021)
Information flow within and between cells depends significantly on calcium (Ca2+) signaling dynamics. However, the biophysical mechanisms that govern emergent patterns of Ca2+ signaling dynamics at the organ level remain elusive. Recent experimental studies in developing Drosophila wing imaginal discs demonstrate the emergence of four distinct patterns of Ca2+ activity: Ca2+ spikes, intercellular Ca2+ transients, tissue-level Ca2+ waves, and a global "fluttering" state. Here, we used a combination of computational modeling and experimental approaches to identify two different populations of cells within tissues that are connected by gap junction proteins. We term these two subpopulations "initiator cells," defined by elevated levels of Phospholipase C (PLC) activity, and "standby cells," which exhibit baseline activity. We found that the type and strength of hormonal stimulation and extent of gap junctional communication jointly determine the predominate class of Ca2+ signaling activity. Further, single-cell Ca2+ spikes are stimulated by insulin, while intercellular Ca2+ waves depend on G?q activity. Our computational model successfully reproduces how the dynamics of Ca2+ transients varies during organ growth. Phenotypic analysis of perturbations to G?q and insulin signaling support an integrated model of cytoplasmic Ca2+ as a dynamic reporter of overall tissue growth. Further, we show that perturbations to Ca2+ signaling tune the final size of organs. This work provides a platform to further study how organ size regulation emerges from the crosstalk between biochemical growth signals and heterogeneous cell signaling states.